Variação diurna das respostas fisiológicas e eficácia Analgésica do tramadol em asininos - Paiva, Ariana Lopes Correia de (Universidade Federal Rural do Semi-Árido, 2016)
We aimed to assess whether cortisol and the physiological variables of asinine are influenced by meteorological variables, and if tramadol at doses of 2.5mg.kg-1 and 4mg.kg-1 IV promotes post-surgical analgesia in donkeys that have undergone orchiectomy. A priori, we used 10 north-eastern donkeys, in which we evaluated heart (HR) and respiratory (fR) rates, systolic (SBP), diastolic (DBP) and mean (MBP) blood pressure, rectal temperature (RT) and cortisol. The weather station of UFERSA provided temperature of the environment (TE), relative humidity (RH) and wind speed (WS) values, from which we calculated the temperature and humidity index (THI) every 2 hours for 24 hours. Afterwards, 24 donkeys, divided into 3 groups of 8 animals each: CG (control group, saline IV), GT2.5 (2.5 mg.kg-1 of tramadol IV) and GT4.0 (4.0 mg.kg-1 of tramadol IV) either received or did not analgesic after castration. The physiological variables mentioned above were re-evaluated and inserted in a multifactorial numerical scale to assess the analgesia within 1h, 2h, 4h, 6h, 8h, 12h and 24h after surgery. Statistical differences between groups in each hour and between hours for each particular group were obtained through the Kruskal-Wallis and Friedman tests, respectively. The relationship between the physiological and meteorological variables were analysed through the Spearman correlation. In the cortisol and physiological variables applied Principal Component Analysis (PCA). HR did not change significantly. The RT rose from 6h until 18h, the fR until 20h, and the blood pressures peaked at 2h and 14h. TE rose significantly from 6h to 14h, the WS until 12h, while the RH decreased until 12h. From 8h until 24h THI was in the range of 71-78, considered critical, its highest average occurred at 14h. There was significant negative correlation between fR and WS, as well as between RT and WS; and positive between fR and RH. Cortisol increased at 6h, peaking every 6h. The mean pain scores in the tramadol groups were significantly lower than those in the CG at 4h after surgery. In total, 87.5% of the GT4.0 animals received rescue analgesia, against 100% of the other groups. We concluded that the meteorological variables influence the physiological variables of donkeys in the north-eastern semi-arid. Tramadol at doses of 2.5 and 4.0 mg.kg-1 IV increased postsurgical analgesia for a period of 4-6h in donkeys that had undergone castration. The doses used did not cause deleterious changes to the cardiovascular parameters of the asinine
Keywords: Jumento Nordestino; Adaptação climática; Castração; Opioide; North-eastern donkey; Climate adaptation; Castration; Opioid; CIENCIAS AGRARIAS::MEDICINA VETERINARIA